Mathematical Connections Of Students Based On Learning Style Using Blended Learning - N K Dwidayati, Hardi, H Suyitno, Kartono, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the process of learning mathematics many students can not make connections in mathematics, thus causing the ability of students in mathematical connections to be low. This problem is characterized by insufficient methods and approaches to improve math achievement in students.The purpose of this study was to find out the difference in mathematical connection ability of students of Madrasah Ibtidaiyah Teacher Education (PGMI) IAIN Surakarta reviewed from the learning style by using blended learning. Based on the results of the study showed that there are differences in the ability of mathematical connections of students who use blended learning and expository. Blended learning tends to have higher value than expository learning. Indicators of connection with other science disciplines scored highest for both control and experiment classes. As for the learning style in the highest comprehension experiment class for mathematical connections, students have the type of audio learning style while the lowest for visual learning style type.